Fuzzy with PID based Sensorless Brushless DC Motor Control - Bagavathy, S.; Maruthupandi, P.; Sheebarani, S.; ., Radhika; Rani N, Ramya (International Journal of Engineering and Technology, 2018)
In this Work, the controller with fuzzy and PID used to execute the speed calculation of a brushless dc motor. The proposed strategy is basic and solid. Amid regenerative braking mode, it saves energy in a rechargeable battery. The proposed controller is coordinated utilizing the fuzzy logic toolbox in MATLAB. The work proposes the idea of fuzzy with PID controller for controlling the speed of BLDC motor. The goals of the undertaking are to analyze the execution of PI and the proposed fuzzy with PID controllers utilizing MATLAB software for the controlling the speed of BLDC motor. The executions of the two controllers are compared based on different control framework time domain parameters. Simulation consequences of the two controllers have been exhibited and it is discovered that the control idea with fuzzy with Â PID controller outflanks customary controller in a large portion of the angles.Â Â